Land abandonment and the dynamics of agricultural landscapes in Mediterranean mountain environments: the case of Ribagorça (Spanish Pyrenees) - Sancho-Reinoso, Alexis (ERDKUNDE, 2013)
This article examines the territorial changes that have occurred in the Pyrenean region of Ribagorça (Spain) over the last 150 years by analysing the evolution in its land cover and land uses. The study focuses on one specific area of this region that is highly illustrative of Mediterranean mountain environments. To do so, it adopts a qualitative approach and takes as its starting point the concept of the agricultural landscape. The results indicate a gradual decline of the region in terms of its ecological, human and cultural elements. Beginning in the second half of the nineteenth century, the decline accelerated through the 1960s, and continues virtually unabated to the present day. The outcome is interpreted here as an “abandoned agricultural landscape”. The article concludes by reflecting critically on the fact that the current model of land colonisation in the region is leading to the simplification, if not the complete disappearance, of the landscape as a complex reality; that is, the arena in which the multiple relations between man and the environment manifest themselves.